The changing role of the salesperson: how should salespeople act today? - Castro-González, Sandra; Bande Videla, Belén (Development and Learning in Organizations, 2020)
Purpose: The purpose of this paper is to highlight the nature and the organizational role of salespeople and, in particular, underscore the change in salespeople’s management in the current business context. Design/methodology/approach: The paper briefly explains the role of salespeople in an organization and how salespeople are gaining prominence in customer management. From this point of view, the paper suggests steps to achieve the sale. Findings: It is evident that salespeople must change the way they achieve sales goals within the organization. Currently, they need to adopt a more customer-centric approach, and the paper suggests how to do this. Practical implications: The paper aims to provide key points for understanding and managing the sales force within the organization. Findings are relevant for those who must manage these workers or those who simply want to know more about the characteristics of the sales force. Originality/value: The paper highlights the importance of salespeople in organizations and describes how they should be managed. In addition, in some ways, the paper helps improve readers’ perception of the sales position.
Keywords: salespeople; sales managers; Scopus